2016
DOI: 10.3389/fchem.2016.00034
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Putative 11-epi-Lyngbouilloside Aglycon

Abstract: We report here the total synthesis of 11-epi-lyngbouilloside aglycon. Our strategy features a Boeckman-type esterification followed by a RCM to form the 14-membered ring macrolactone and a late-stage side chain introduction via a Wittig olefination. Overall, the final product was obtained in 20 steps and 2% overall yield starting from commercially available 3-methyl-but-3-enol. Most importantly, the strategy employed is versatile enough to eventually allow us to complete the synthesis of the natural product an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Rawal demonstrated that glyoxolate electrophiles could benefit similarly to the aforementioned chelation system using TADDOL hydrogen‐bond donors to allow for high selectivity . Notably, in their recent total synthesis of lyngbouilloside, Cossy disclosed that using vinylogous Mukaiyama conditions did not provide their desired β‐hydroxydioxinone adduct in a stereoselective manner, requiring them to use preparative supercritical fluid chromatography to separate the enantiomers . These examples, combined with previous methods that are only practically selective for sp 2 ‐type substrates highlight situations where there is limited enantio‐ and diastereocontrol, force the need for step‐uneconomical processes .…”
Section: Figurementioning
confidence: 99%
“…Rawal demonstrated that glyoxolate electrophiles could benefit similarly to the aforementioned chelation system using TADDOL hydrogen‐bond donors to allow for high selectivity . Notably, in their recent total synthesis of lyngbouilloside, Cossy disclosed that using vinylogous Mukaiyama conditions did not provide their desired β‐hydroxydioxinone adduct in a stereoselective manner, requiring them to use preparative supercritical fluid chromatography to separate the enantiomers . These examples, combined with previous methods that are only practically selective for sp 2 ‐type substrates highlight situations where there is limited enantio‐ and diastereocontrol, force the need for step‐uneconomical processes .…”
Section: Figurementioning
confidence: 99%
“…It is worthy to note, efforts by Hoye and coworkers in 2008 who reported a dual macrolactonization/pyran–hemiketal formation event using acylketenes with applications to the synthesis of (−)‐callipeltoside A and a lyngbyaloside B model systems [16] . In their synthesis of 1 a , Cossy proposed the aforementioned revised structure of lyngbouilloside with stereochemical reassignment of the C11 stereogenic center as the C11‐epimer, and thus a potential C10/C11 syn relationship that the authors would later revisit in a 2016 report, vide infra [17] …”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Cossy and coworkers, [17] reported an elegant total synthetic effort to the putative 11‐epi‐lyngbouilloside aglycon featuring a Boeckman esterification, RCM strategy to form the 14‐membered ring macrolactone, Wittig olefination for late‐stage sidechain introduction, and a glycosylation for installation of rhamnose. In this work, the authors provided careful and detailed analysis of the spectroscopic data (see detailed 13 C table) of their synthetic product with the original data reported for lyngbouilloside, and noted that discrepancies still remained.…”
Section: Introductionmentioning
confidence: 99%